Kesiapan Siswa dalam Menghadapi Pembelajaran Digital: Analisis Bibliometrik - Thahir, Muthahharah; Amalia, Kaniati; Thahir, Wahyuni; Widiawati, Widiawati; Asri, Kholifatul Husna; Nurlatifah, Siti (Indonesian Journal of Educational Counseling, 2023)
This study aims to map the results of publications on the topic of student readiness and digital learning. The method used is bibliometric analysis. The data used in this research comes from CrossRef. The data search is carried out through the Publish or Perish application. The search results yielded a total of 599 articles in English. The keywords used to search for articles are "Student Readiness" and "Digital Learning". The results of this study indicate that research on student readiness is still small when compared to research on digital learning topics. In addition, there is no research that directly analyzes how students are prepared to face digital learning, this can certainly be novelty for future researchers who will research digital learning. The suggestion from this study is that researchers conduct research related to student learning readiness in digital learning such as student readiness in distance learning or student readiness in using digital learning media.